Original paperComparing a volume based template approach and ultrasound guided freehand approach in multicatheter interstitial accelerated partial breast irradiation - Koh, Vicky Y.; Buhari, Shaik A.; Tan, Poh Wee; Inn Tan, Yun; Leong, Yuh Fun; Earnest, Arul; Tang, Johann I. (Journal of Contemporary Brachytherapy, 2014)
Purpose : Currently, there are two described methods of catheter insertion for women undergoing multicatheter interstitial accelerated partial breast irradiation (APBI). These are a volume based template approach (template) and a non-template ultrasound guidance freehand approach (non-template). We aim to compare dosimetric endpoints between the template and non-template approach. Material and methods: Twenty patients, who received adjuvant multicatheter interstitial APBI between August 2008 to March 2010 formed the study cohort. Dosimetric planning was based on the RTOG 04-13 protocol. For standardization, the planning target volume evaluation (PTV-Eval) and organs at risk were contoured with the assistance of the attending surgeon. Dosimetric endpoints include D90 of the PTV-Eval, Dose Homogeneity Index (DHI), V200, maximum skin dose (MSD), and maximum chest wall dose (MCD). A median of 18 catheters was used per patient. The dose prescribed was 34 Gy in 10 fractions BID over 5 days. Results : The average breast volume was 846 cm 3 (526-1384) for the entire cohort and there was no difference between the two groups (p = 0.6). Insertion time was significantly longer for the non-template approach (mean 150 minutes) compared to the template approach (mean: 90 minutes) (p = 0.02). The planning time was also significantly longer for the non-template approach (mean: 240 minutes) compared to the template approach (mean: 150 minutes) (p < 0.01). The template approach yielded a higher D90 (mean: 95%) compared to the non-template approach (mean: 92%) (p < 0.01). There were no differences in DHI (p = 0.14), V200 (p = 0.21), MSD (p = 0.7), and MCD (p = 0.8). Conclusions : Compared to the non-template approach, the template approach offered significant shorter insertion and planning times with significantly improved dosimetric PTV-Eval coverage without significantly compromising organs at risk dosimetrically.